“La incidencia de las redes sociales en la rentabilidad micro empresarial de la Ciudad de Loja, periodo 2019-2020” - Riofrío Pogo, Janeth Esperanza (2021)
The main objective of this investigation is to know "The incidence of social networks in the micro business profitability of the city of Loja, period 2019-2020", based on a study of situational analysis to microenterprises in the city, as the first point is the introduction where the order in which the work is structured giving an exact idea of various aspects studied, followed by the literature review, which allowed us to obtain relevant bibliographical information that helped us to support the investigation. Subsequently, the theoretical framework addressed themes related to the different digital platforms that exist and their use in microenterprises in Latin America and Ecuador. The methodology used for the development of the study is exploratory and descriptive research, in addition, a survey was applied through non-probabilistic sampling by convenience, where a series of questions were analysed and interpreted, which allowed us to identify the main problems faced by micro-entrepreneurs. The results include themes related to the situational analysis of the macro environment, analysing the PEST variables with respect to the current situation in the country, and an analysis of the micro and macro environment, focusing directly on the city of Loja. The survey was applied to the selected sample (105 micro entrepreneurs), with the objective of finding out the social networks that are most used and the level of trust that social networks give micro entrepreneurs to trust the advertising of their microenterprises, this analysis was carried out using the IBM SPSS programme, which allowed for a comparative analysis of each of the variables involved in the survey. In the discussion, the importance of the reinvention of microenterprises in the current time is detailed, analysing the social networks Facebook, Instagram and the messaging network Whatsapp categorised as the most important, this in relation to the economic sector to which their microenterprises belong, This analysis was carried out by 4 means of a cross table of variables provided by the IBM SPSS programme. An analysis was also carried out on the most used digital platforms and their influence on the improvement of the sales of the microenterprises, and the level of importance that the micro entrepreneurs show when investing in advertising on social networks was also studied; Finally, the conclusions obtained from the investigation were presented and recommendations were made for strategies that will give microenterprises an advantage over others by using social networks as the main tool.